2021
DOI: 10.3897/pharmacia.68.e70292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of esomeprazole on lipid profile in patients with peptic ulcer

Abstract: Esomeprazole; a newly introduced PPI has been widely prescribed by healthcare providers due to its improved pharmacokinetic profile. Most users could have other diseases and the PPIs are indicated as acid-suppressor to minimize gastric side effects of polypharmacy. A high percentage of users could suffer from cardiovascular diseases and lipid dysmetabolism. Hence, this study was designed to determine the impact of long-term use of esomeprazole on lipid profile in a normal subject other than having peptic ulcer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The biochemical findings of renal and liver function tests together with histological study revealed that propolis has provided a protection against modulation induced by isoniazid and rifampicin though measured parameters. Drug side effects on various vital organs has been reported, antipsychotics affect immunity (18), allopurinol on metabolic parameters (19) and thyroid function (20), statins on platelets (21) and metabolic parameters (22), antidiabetics on thyroids (23), non-steroidal anti-inflammatory drugs on gastric mucosa (24), proton-pump inhibitors on kidneys (25) and metabolic parameters (26). These effects depicted in our locality and using propolis as an add-on therapy might restore the defective actions.…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical findings of renal and liver function tests together with histological study revealed that propolis has provided a protection against modulation induced by isoniazid and rifampicin though measured parameters. Drug side effects on various vital organs has been reported, antipsychotics affect immunity (18), allopurinol on metabolic parameters (19) and thyroid function (20), statins on platelets (21) and metabolic parameters (22), antidiabetics on thyroids (23), non-steroidal anti-inflammatory drugs on gastric mucosa (24), proton-pump inhibitors on kidneys (25) and metabolic parameters (26). These effects depicted in our locality and using propolis as an add-on therapy might restore the defective actions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the activity of both extracts was more in yeast than in bacteria. 22 As an antioxidant, extract of these plants could find an application in a wide range of chronic diseases which are associated with oxidative stress, such as, diabetes, [23][24][25][26] hyperlipidemia, 27,28 metabolic syndromes, 29 ulcerative diseases, [30][31][32][33] and thyroid disorders. 34 The potency of these plant extracts could be comparable to commonly used antioxidant vitamins in terms of potential therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial outcome of the present study induced by beta carotene should be considered in the protection of renal system from the destructive effects of other chronically used drugs, if any. For example, statins (41,42), proton-pump inhibitors (43,44), CNS drugs (45,46), chemotherapeutic agents (47,48), drug used for diabetes (49,50). Moreover, the same positive effects obtained from beta carotene could be provided by other harmless OTC drugs, such as, vitamins (51,52), or minerals (53,54), or herbal remedies (55) or xanthine oxidase inhibitors (allopurinol) (56,57).…”
Section: Discussionmentioning
confidence: 99%